Sexual Self-schema, Perceptions of Breast Talk, and Physical Self-concept in Breast Cancer Survivor - Juneman Abraham; Miranti Ayu Puteri (Intelektual Pustaka Media Utama, 2015)
The quality life of breast cancer survivors has been the psychology’s focus of attention. However, studies discussing their sexuality highlighted from the social psychology perspective are still not very much, especially in Indonesia. This study aimed to predict sexual self-schema of breast cancer survivors based on their perceptions of the breast talk and physical self-concept. This study used a predictive-correlational design and employed psychological scales measuring instruments, multiple linear regression data analysis technique as well as purposive sampling method. This study was conducted on 130 women breast cancer survivors (Mage = 39.45 years old; SDage = 3.542 years; all been married) in Special Capital Region of Jakarta - the capital city of Indonesia, and its surrounding areas (Bogor, Tangerang, and Bekasi). The study results showed that the perception of functional breast talk and physical self-concept are able to predict sexual self-schema in positive directions. Other perceptions of breast talk (medicalized, gendered, and sexualized breast talk) are not able to predict it. This study has important implications in order to improve the life quality of the survivors, namely by managing fair discourses about breast in the public and keeping the proper physical self-concept since the early stage of life.